2007
DOI: 10.1007/s10555-007-9091-x
|View full text |Cite
|
Sign up to set email alerts
|

The Nedd4-like family of E3 ubiquitin ligases and cancer

Abstract: Accumulating evidence suggests that E3 ubiquitin ligases play important roles in cancer development. In this article, we provide a comprehensive summary of the roles of the Nedd4-like family of E3 ubiquitin ligases in human cancer. There are nine members of the Nedd4-like E3 family, all of which share a similar structure, including a C2 domain at the N-terminus, two to four WW domains in the middle of the protein, and a homologous to E6-AP COOH terminus domain at the C-terminus. The assertion that Nedd4-like E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(197 citation statements)
references
References 161 publications
(271 reference statements)
4
193
0
Order By: Relevance
“…1 Laine et al, 13 reported that UV-irradiation or g-irradiation decreases WWP1 mRNA expression in mouse embryonic fibroblasts in a p53-dependent manner. However, we found that several DNA damage chemotherapeutic drugs including doxorubicin, cisplatin and etoposide induces the WWP1 expression in HCT116 and breast cell lines in a p53-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Laine et al, 13 reported that UV-irradiation or g-irradiation decreases WWP1 mRNA expression in mouse embryonic fibroblasts in a p53-dependent manner. However, we found that several DNA damage chemotherapeutic drugs including doxorubicin, cisplatin and etoposide induces the WWP1 expression in HCT116 and breast cell lines in a p53-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…1 All family members share a distinctive domain structure: a C2 domain at the N terminus for calcium-dependent phospholipid binding, 2-4 WW domains in the middle for protein-protein interaction with PY motifs, and a HECT domain at the C terminus for the ubiquitin transfer. Four family members including WWP1, 2,3 NEDD4, 4 SMURF1, 5 and SMURF2, 6 have been shown to be overexpressed in different tumor types.…”
mentioning
confidence: 99%
“…EPS15 and Cbl have been demonstrated to be RNF11-interacting proteins in yeast two-hybrid experiments (Azmi and Seth, 2005). WWP1 has been shown to increase the ubiquitination of EPS15 (Woelk et al, 2006;Chen and Matesic, 2007). In addition, a WWP1 family member, Itch/AIP4, has been shown to promote Cbl ubiquitination (Magnifico et al, 2003).…”
Section: Wwp1 Upregulates Erbb2 and Egfr Through Rnf11mentioning
confidence: 99%
“…The WW domain containing E3 ubiquitin protein ligase 1 (WWP1/AIP5/Tiul1) belongs to the Nedd4-like homologous to the E6-associated protein C terminus (HECT)-type E3 family (Chen and Matesic, 2007). Nedd4-like E3s can be identified by their distinctive domain structure: an HECT domain at the C terminus for the ubiquitin transfer (Verdecia et al, 2003), a C2 domain at the N terminus for calcium-dependent phospholipid binding, and 2-4 WW domains in the middle for protein-protein interaction with PY motifs (Mosser et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The WW domain containing E3 ubiquitin protein ligase 1 (WWP1) belongs to the C2-WW-HECT type E3 family, which comprises of nine members including AIP4/Itch and WWP1 (Chen and Matesic, 2007). The N-terminal C2 domain is responsible for calciumdependent phospholipid binding.…”
Section: Introductionmentioning
confidence: 99%